Role of Tropomodulins in brain physiology and pathology - Chuan Hong; Xiaopeng Liu; Zhou Zhou; Yuan Xing; Zixuan Cao; Yan-Zhong Chang; Guofen Gao (Neurobiology of Disease)
Actin dynamics are crucial for the morphogenesis and function of neurons in the brain. Tropomodulins (Tmods) belong to a family of actin-binding proteins that cap the pointed-end of actin filaments. There are four Tmod isoforms, and three of which, Tmod1, Tmod2 and Tmod3, are expressed in the brain, with Tmod2 exhibiting neuronal specific expression. By regulating actin filament dynamics, Tmods participate in neurite outgrowth, dendritic spine formation, and synaptic morphology, thereby contributing to structural and functional neural plasticity. Dysregulation of Tmods has been demonstrated in several neurodegenerative and neuropsychiatric diseases, such as Alzheimer's disease, epilepsy, Down syndrome, and addictive behaviors. Currently, compared to cancer and cardiovascular diseases, the roles and mechanisms of altered Tmod expression in neurological diseases remain poorly understood. In this article, we provided an overview on the physiological roles and crucial functions of Tmods in the brain, summarized the recent advances in alterations of Tmods in neurodegenerative and neuropsychiatric diseases, and discussed their implications and potential contributions to disease pathology and treatment. This review may expedite future studies to delineate the roles and molecular mechanisms of Tmods in brain physiology and pathology, ultimately promoting the development of novel diagnostic and therapeutic strategies for related neurological diseases.